Establishing a Law and Psychiatry Clinic - Eric S. Janus; Maureen Hackett (Washington University Journal of Law & Policy, 2004)
Psychiatry and law are interdependent to an extent exceeded by few other pairs of professions. As a result, psychiatrists and other mental health professionals (“MHPs”) can wield tremendous power in legal settings. In their Law and Psychiatry Clinic, William Mitchell College of Law and the Department of Psychiatry of the University of Minnesota School of Medicine work at the boundaries of their fields. By adopting a centralized and integrated model for interdisciplinary clinical education, the clinic allows both professions to gain professional and cross-professional competence and understanding. Given the determinative role often played by psychiatry in law, the clinic hopes that its work will lead to more transparency and mindfulness in the use of psychiatric expertise, and therefrom, to an increase in the quality of justice. We begin with a brief description of the development of the clinic, describing its functioning and the particular structure we have adopted for it. We then turn to the educational objectives of the clinic, which leads to our discussion of implementation problems. After offering some evaluative comments about the clinic, we close by discussing the ways in which it might contribute to an increase in justice.
Keywords: Clinical legal education; Psychiatry; Interdisciplinary approach in education